Comparasion Analysis of Video Quality on Codec VP8 and H.265 PBX Server with Pixel Conversion Method - Riza Rosyidah Adi Putri; Martono Dwi Atmadja; Mochammad Junus (Jurnal Jaringan Telekomunikasi, 2022)
Many studies and research are continuously being developed to improve the quality and capability of video compression. Compression of the video is done with the help of a video codec, in the video there are several types of video codecs including VP8 and H.265. These two codec models have very high resolutions for video. In implementing video calls, the determination of the codec has not been able to prove the results of video quality. To be able to know the quality of the resulting video, codec quality testing can be done through pixel conversion which can later be analyzed for video quality when making calls. In this study, a comparison of the performance of the VP8 and H.265 codecs will be carried out using the FreePBX server as a Raspberry Pi-based Video Call Server and is expected to find out which codecs are appropriate to use for the video call process. Based on the results of the comparison study between the two codecs, it shows that the value of the QoS parameter includes packet loss codec H.265 with a resolution of 720 lower with a value of 0.95%. The throughput value of the VP8 codec with 720p resolution is higher with a value of 1275.36 Kbps. The delay value in the H.265 codec with VGA resolution lower with a value of 6.78 ms. The results of the pixel conversion test show that the H265 codec has a higher PSNR value of 55.64 dB and a lower MSE value of 5.66.